2017
DOI: 10.1038/emm.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota in T-cell homeostasis and inflammatory diseases

Abstract: The etiology of disease pathogenesis can be largely explained by genetic variations and several types of environmental factors. In genetically disease-susceptible individuals, subsequent environmental triggers may induce disease development. The human body is colonized by complex commensal microbes that have co-evolved with the host immune system. With the adaptation to modern lifestyles, its composition has changed depending on host genetics, changes in diet, overuse of antibiotics against infection and elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 100 publications
(152 reference statements)
2
124
0
3
Order By: Relevance
“…Multiple studies have revealed that bacterial stimulation is important for mucosal T cell responses and in particular important for balancing the ratio between Tregs and effector T (Lee and Kim, 2017). In the current study, a consortium consisting of Escherichia/Shigella, Klebsiella (Gammaproteobacteria), Bifidobacterium, and four genera belonging to Firmicutes, for which the relative abundance in the small intestine were higher in the amoxicillin group than in controls, positively correlated with the fraction of small intestinal Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed that bacterial stimulation is important for mucosal T cell responses and in particular important for balancing the ratio between Tregs and effector T (Lee and Kim, 2017). In the current study, a consortium consisting of Escherichia/Shigella, Klebsiella (Gammaproteobacteria), Bifidobacterium, and four genera belonging to Firmicutes, for which the relative abundance in the small intestine were higher in the amoxicillin group than in controls, positively correlated with the fraction of small intestinal Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their digestive function, bacteria within the gut are also important for maturation of the immune system and can modulate the immune response by both promoting certain functions and triggering anti-inflammatory responses. [9][10][11][12] The composition of the microbiota is fluid as alterations in diet and the presence of non-infectious disease have been shown to shift certain subpopulations within the gut microbiota. 13,14 These resulting communities can also induce phenotypic traits when administered to gnotobiotic mice.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, allergic diseases were considered to be mainly caused by an imbalance of functional CD4+ T-cell subpopulations, including an imbalance of Th1/Th2 immune responses, allergic inflammation characterized by Th2-mediated hyperactivity, and inhibition of Th1 responses [1]. Recently, other T-cell subsets (e.g., Th17/Treg cells) have also been confirmed to be involved in the immunomodulation of allergic diseases [2]. Among these populations, Treg cells have been widely studied in light of their important role in inhibiting the migration and differentiation of other effector and inflammatory cells [3].…”
Section: Introductionmentioning
confidence: 99%